Abū Bakr al-Fūrakī, référence ašʿarite inconnue du Traité de théologie d’Averroès - Canova, Barbara (Annali di Ca’ Foscari: Serie Orientale, 2025)
Averroes’ kalām treaty, the Kitāb al-kašf ʿan manāhiğ al-adilla is one of the most controversial texts from the Andalusian philosopher. Its writing relied vastly on Aristotelian texts and opuses from the aš‘arite kalām, of which Averroes wanted to deconstruct and refute the doctrines. Most of its references – whether they are Aristotelian or ašʿarite are not explicitly quoted – are consistent with the medieval Islamic customs. Having published between 2005 and 2007 an analysis of the Aristotelian sources of this text, this contribution aims at studying the ašʿarite authors critiqued by Averroes and broadly mentioned as the ‘modern ašʿarites’. The main source discovered through this textual comparison is the Kitāb al-Niẓāmī fī usūl ad-dīn by Abu-Bakr Al-Fūrakī, author of a kalām treaty of which a single copy has been conserved in Istanbul. A transcription and a translation of its most salient excerpts have been included in this contribution, in order to show the relationship between those two kalām treaties.